Historyczna mikrotoponimia Podlasia w źródłach notarialnych - Kuć, Joanna (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
The article shows and describes names of small rural spaces registered in the 19th century notarial acts from the area of Łuków. There are over 300 units, the names of the so called lands, semantically and structurally varied, excluding the names of waterways that are not represented in the research material. The way of description of these microtoponyms doesn’t leave any doubt that they are proper names being connected with locating and characterizing functions, serving as landmarks in defining the borders of fields, meadows, forests and succession possessions. The material from Łuków reveals the specific concentration of names, including topographic motivation, having the largest share in the creation of these units, followed by possessive and cultural ones. These names are generally, structurally and semantically transparent with reference to the historical names of Mazovia.